Integrating Molecular and Biochemical Findings in β-Thalassemia Major for Improved Pharmacotherapy , Iraq - JABER, Muntadher Mohammed; Nayyef, Hussein Ali; mohaisen, Sarab abbas; ABBAS, Adyan Nafea (Adolescência e Saúde, 2026)
Beta thalassemia is one of the most prevalent genetic disorders worldwide and a common inherited condition affecting newborns when parents are carriers or affected. It represents a severe form of anemia associated with multiple clinical complications. This study aimed to evaluate hematological and biochemical markers in patients with beta thalassemia major in Thi Qar province, Iraq, with a focus on monitoring treatment outcomes and improving pharmacological management, including the effectiveness of iron chelation therapy.A total of 100 transfusion-dependent beta thalassemia patients and 100 healthy controls were included. Most patients received regular blood transfusions along with iron chelation therapy, mainly deferoxamine. However, many patients still exhibited elevated serum ferritin levels, suggesting inadequate chelation or poor compliance. Hematological analysis revealed significantly lower values in patients compared to controls, including hemoglobin (Hb), hematocrit (PCV), mean corpuscular volume (MCV), and mean hemoglobin (p<0.05–0.01), while mean corpuscular hemoglobin concentration (MCHC) showed no significant difference (p>0.05). Biochemical findings indicated increased levels of blood glucose, triglycerides, alkaline phosphatase (ALP), alanine transaminase (ALT), aspartate transaminase (AST), and kidney function markers in patients. Lipid profile analysis showed lower LDL and HDL levels in controls. No significant differences were observed in serum albumin, calcium, sodium, and potassium levels (p>0.05). Additionally, primary hypothyroidism was identified in 5.31% of patients, characterized by elevated thyroid-stimulating hormone (TSH >4.5 mIU/L) and reduced T4 levels (<5.6 mIU/dL). This study highlights the importance of continuous monitoring and comprehensive evaluation of beta thalassemia patients to optimize treatment strategies and improve clinical outcomes.